Security, privacy, and forensics issues in big data - Joshi, R. C.; Gupta, Brij, 1982- (Advances in information security, privacy, and ethics (AISPE) book series., 2020)
"This book focuses on the security, privacy, and forensics of big data. It also examines the principles, algorithms, challenges and applications related to the security, privacy, and forensics of big data"--